Migrants and Their Life Stories: Perspectives on Education, Work, and Community - Angeloni, Brigida (INSTED: Interdisciplinary Studies in Education & Society, 2021)
Men and women who leave their countries, families, education, and work, undertake a hard journey. Some are fleeing war, others terrorism, others poverty; they are looking for solutions, either for themselves or their loved ones. Some need medical care that they cannot access in their home country. Each one has their own story and we simply do not know enough about them. Migrants’ life histories can provide us with a lot of useful information that can help us understand the contemporary phenomenon of migration from pedagogical, sociological and economic points of view. The paths and trajectories of entire communities remain unknown, their needs unheard, and the enormous value they bring in terms of new relationships, mutual help and competences is neither brought to light nor properly evaluated. This article, born from a series of biographical interviews carried out with adult migrants from countries in west Africa, reflects on the relationship between education, work, and the communities to which the migrants belong.